Theme and Rheme in Children Online Stories by English Native and Indonesian Authors - lisa karlina; Rismiyanto Rismiyanto; Fitri Budi Suryani (SIMPLE: International Journal of English Education, 2026)
Children online stories represent a modern evolution of traditional storytelling, where classic tales and original narratives are shared through digital platforms rather than printed books. In the context of language and education, children online stories are also valuable tools for language acquisition and discourse analysis. The way information is structured, how themes (what the story is about) and Rhemes (what is said about it) are organized. They can influence how children comprehend the text and internalize the message. This study investigates how theme and rheme structures operate in children online stories written by English native (The Fox and The Crow, Little Red Riding Hood) and Indonesian authors (The Mousedeer and The Crocodile and Bawang Merah Bawang Putih). By exploring the use of thematic progression within selected texts, the research seeks to uncover narrative patterns influenced by linguistic and cultural contexts. The core research problem addresses how English native authors and Indonesian authors differ in their arrangement of theme and rheme. The objective is to compare the structural use of topical, interpersonal, textual themes and thematic progression in selected twelve fables and twelve folktales Indonesian stories in English version and English originated stories. This study adopts a qualitative approach using purposive sampling to select four representative texts. The analysis applies Halliday and Matthiessen Systemic Functional Linguistics (2004), focusing on clause level theme identification and thematic progression across the stories. Findings reveal that English native authors tend to use a wider range of interpersonal and textual themes to develop reader engagement and consistency, while Indonesian authors prioritize topical themes to convey moral clarity and cultural norms. This divergence reflects differing narrative priorities and strategies rooted in linguistic traditions. The study concludes that theme and rheme structures in children stories are not only textual mechanisms but also carriers of cultural meaning. The implications support cross cultural literacy development and inform educators, translators, and curriculum designers in fostering inclusive and culturally responsive literature for children.